2006
DOI: 10.1007/s10935-006-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Causes of and Solutions for School Violence: Implications for Policy

Abstract: This study explores perceptions of causes of and solutions for school violence in a sample of 202 parents interviewed in the wake of nationally publicized school shootings. We also investigate the effects the school shootings had on children, parents' perceptions regarding firearms, and changes in parenting behavior. Parents exhibited strong support for almost all proposed causes and solutions, and we address their desire for immediate and often invasive interventions to prevent future violence. We contrast pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Despite the increasing awareness of the importance of familyschool collaboration for effective school-based violenceprevention programs, few schools are able to successfully engage parents in these types of efforts (Berger, 2007;Bliss, Emshoff, Buck, & Cook, 2006;Bradshaw, Zmuda, Kellam, & Ialongo, 2009). As such, additional research is needed to determine factors that increase parent involvement in school-based violenceprevention programming.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Despite the increasing awareness of the importance of familyschool collaboration for effective school-based violenceprevention programs, few schools are able to successfully engage parents in these types of efforts (Berger, 2007;Bliss, Emshoff, Buck, & Cook, 2006;Bradshaw, Zmuda, Kellam, & Ialongo, 2009). As such, additional research is needed to determine factors that increase parent involvement in school-based violenceprevention programming.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…It was also made evident that while previous research has made it clear that building positive relationships and increasing student connectivity are key components toward decreasing school violence, the purpose of this research was to discover the perspectives of employees in regards to responding to a school shooting that was already in progress. (Daniels et al, 2007;Daniels et al, 2010;Bliss et al, 2006).…”
Section: Methods Of Proceduresmentioning
confidence: 99%
“…Previous research has suggested that in order to prevent school shootings it is important that schools focus on developing relationships and making sure students feel connected to their school, however this is something that can take years to develop. (Daniels et al, 2007;Daniels et al, 2010;Bliss et al, 2006).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…One study I found showed that parents held insufficient positive parenting as an important factor in the prevalence of school-based violence (Bliss, Eimshoff, Buck, & Cook, 2006). They favored programs that encouraged increased parental involvement in the schools and at home with children.…”
Section: What Do Parents Think?mentioning
confidence: 99%